2022
DOI: 10.1007/s11356-022-21844-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly adsorption and sensitive detection of Hg (II) by biomass-derived nitrogen-doped carbon dots: process modelling using central composite design

Abstract: In this study, luminescent bio-adsorbent nitrogen-doped carbon dots (N-CDs) was produced and applied for the removal and detection of Hg (II) from aqueous media. N-CDs were synthesized from oil palm empty fruit bunch carboxymethylcellulose (CMC) and urea. According to several analytical techniques used, the obtained N-CDs display graphitic core with an average size of 4.2 nm, are enriched with active sites, stable over a wide range of pH and have great resistance to photobleaching. The N-CDs have bright blue e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The results of UV-Vis absorption spectroscopy tests performed on it ( Figure S3a ) showed that an absorption peak near 215 nm could be attributed to a π-π* leap in the C=C bond [ 32 , 33 , 34 ]. In contrast, the absorption near 345 belongs to the n-π* leap of C=O/C=N [ 35 , 36 ]. In addition, Figure S3b shows the strong emission (λem = 487 nm) under optimal excitation (λex = 414 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The results of UV-Vis absorption spectroscopy tests performed on it ( Figure S3a ) showed that an absorption peak near 215 nm could be attributed to a π-π* leap in the C=C bond [ 32 , 33 , 34 ]. In contrast, the absorption near 345 belongs to the n-π* leap of C=O/C=N [ 35 , 36 ]. In addition, Figure S3b shows the strong emission (λem = 487 nm) under optimal excitation (λex = 414 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The specific selectivity of N-CQDs toward Hg 2+ among other metal ions can be attributed to the strong coordination of Hg 2+ with the O and N electron donors, which triggers the transfer of excited energy to the dorbital of Hg 2+ , resulting in the quenching of N-CQDs. [145] Zdražil et al [199] synthesized N-doped CQDs using citric acid and amine. These CQDs exhibited a [148] Reproduced with permission: Copyright 2021, Elsevier.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…The specific selectivity of N‐CQDs toward Hg 2+ among other metal ions can be attributed to the strong coordination of Hg 2+ with the O and N electron donors, which triggers the transfer of excited energy to the d‐orbital of Hg 2+ , resulting in the quenching of N‐CQDs. [ 145 ] Zdražil et al [ 199 ] synthesized N‐doped CQDs using citric acid and amine. These CQDs exhibited a turn‐off PL lifetime and an exceptional selectivity for detecting Hg2+ in water, achieving a LOD of 0.7 ppb (3.5 nM), and demonstrated high resistance to photobleaching, maintaining stability under continuous pulsed laser excitation for as long as 38 h.…”
Section: Applicationsmentioning
confidence: 99%
“…This decline could be associated with the precipitation of C-dots at higher temperatures. 79 Wu et al described the fabrication of C-dots from Bombyx mori silk through a single-step hydrothermal process. These C-dots demonstrated good stability under different pH conditions and exhibited negligible fluorescence decay over several weeks of storage.…”
Section: Properties Of C-dotsmentioning
confidence: 99%